(untitled) (Journal of Medical & Health Sciences Review, 2025)
The purpose of this research is to assess the early efficacy of PPCI among uncontrolled DM patients, specifically concerning procedural success, complications and in-hospital mortality. Thus, 350 patients with acute MI treated with PPCI at the tertiary care cardiology center were categorized; 180 patients with uncontrolled DM (HbA1c >7%) and 170 with well-controlled DM (HbA1c ≤7%). The results proved that uncontrolled DM was linked to an increased in-hospital mortality 6.7% and 2.9%, P<0.05 as well as the increased rate of complications involving bleeding 13.9% and 8.8% P>.05) and CI-AKI 11.1%, and 8.8% P>.05. The procedural success rates were 96,1% in uncontrolled DM and 97,0% in controlled DM, therefore there is a fact that although the PPCI efficacy is similar, short-term outcomes of patients with uncontrolled DM are worse due to other health issues. The findings of the study indicate that glycemic control before PPCI may be beneficial in increasing short-term beneficial outcomes, stressing on the impact of glycemic management in the patients with diabetes before performing the coronary intervention treatment.